2019
DOI: 10.1088/1674-1056/28/1/016801
|View full text |Cite
|
Sign up to set email alerts
|

Approximate expression of Young’s equation and molecular dynamics simulation for its applicability

Abstract: In 1805, Thomas Young was the first to propose an equation (Young's equation) to predict the value of the equilibrium contact angle of a liquid on a solid. On the basis of our predecessors, we further clarify that the contact angle in Young's equation refers to the super-nano contact angle. Whether the equation is applicable to nanoscale systems remains an open question. Zhu et al. [College Phys. 4 7 (1985)] obtained the most simple and convenient approximate formula, known as the Zhu-Qian approximate formula … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Molecular dynamics (MD) simulation provides a more direct and effective way to study the nucleation of bubbles from the microscopic perspective. It has been extensively used to study the nucleation of Lennard-Jones liquids [16][17][18][19] and nanobubbles. [20][21][22] Classical molecular dynamics is a computer simulation method used to study the equilibrium and transport properties of a classical many-body system by solving Newton's classical equations of motion for each component.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular dynamics (MD) simulation provides a more direct and effective way to study the nucleation of bubbles from the microscopic perspective. It has been extensively used to study the nucleation of Lennard-Jones liquids [16][17][18][19] and nanobubbles. [20][21][22] Classical molecular dynamics is a computer simulation method used to study the equilibrium and transport properties of a classical many-body system by solving Newton's classical equations of motion for each component.…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers have investigated the nucleation of liquid argon using MD simulation, [18,19,[25][26][27][28][29][30] since the interactions between liquid argon atoms are easy to describe. The results showed that the nucleation rate of liquid argon obtained by MD simulation is 7-9 orders of magnitude higher than that obtained by CNT [26,27] and that nucleation is affected by temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, the syner-gistic effect between the amorphous phase and the crystalline phase is very important, which can be coordinated by adjusting the size of the amorphous phase and crystalline phase. In various experimental and theoretical methods, the method of the molecular dynamics (MD) simulation proves to be useful, particularly in investigating macroscopic and microscopic phenomena of materials, [30][31][32] and it is reliable in revealing the strengthening mechanism and deformation mechanism of metal materials. [33] Here, the effect of the crystalline orientation, the component of the amorphous phase and AB spacing on the deformation behavior of DPMA under tensile loading are investigated by the MD simulation method.…”
Section: Introductionmentioning
confidence: 99%